Experimental research methodology crack opening width of reinforced concrete elements - Колчунов, В.И.; Эддин, Масуд Нур (Proceedings of National Aviation University (archive), 2006)
The tasks of experimental researches have been formulated, basic of which are: definition of width disclosing cracks at a level of the working fixture and in several levels above the stretched fixture; changes of distance between cracks and length of cracks in process of increase of loading with check of multilevel process of formation cracks; definition of deformations of the fixture and concrete with deformation account of effect in a vicinity of a two-console element. The technique of experimental researches of width of disclosing cracks of ferro-concrete designs from a position of the mechanics destruction is developed which has allowed to decide the put tasks.